Effect of oxygen on the corrosion of SiC in LiF–NaF–KF molten salt. (February 2016) - Yang, Xinmei; Liu, Min; Gao, Yantao; Zhang, Dongsheng; Feng, Shanglei; Liu, Huajian; Yu, Guojun; Wu, Guozhong; Wang, Mouhua; Zhou, Xingtai; Xia, Huihao; Huai, Ping; et al.
Highlights: Corrosion of SiC in molten FLiNaK salt was studied. Corrosion resistance of SiC in molten FLiNaK salt can be improved by decreasing oxygen content in SiC. High purity CVD SiC can also be corroded by molten FLiNaK salt, which should be attributed to oxygen impurity in salt. Corrosion of SiC results in the formation of a carbon-rich surface. Corrosion of SiC results in the dissolution of Si from SiC into salt. Abstract: The corrosion of SiC in molten FLiNaK (46.5 mol% LiF, 11.5 mol% NaF and 42 mol% KF) salt was studied. Results reveal that oxygen impurities from SiC and salt can affect the corrosion. SiC with a large amount of oxygen impurity is corroded, whereas high purity SiC is only slightly corroded. SiC can react with oxygen impurity in salt to form oxide and then corroded by the cleavage of SiOSi bond. Corrosion decreases the Si content in SiC, resulting in formation of a carbon-rich surface. A portion of excess C reacts with F to form CF bonds.